The significance of reactive oxygen species in the formation of calcium oxalate stones and the protective effects of antioxidants on the kidneys - Ying, XiaoLong; Chen, Yang; Hao, ZongYao; Liu, HaoRan (Frontiers in Immunology, 2025)
Exposure of renal tubular epithelial cells (RTCs) to kidney stones or calcium oxide crystals triggers the production of reactive oxygen species (ROS), leading to oxidative stress. This oxidative milieu incites cellular injury and elicits an inflammatory cascade within the RTCs. Notably, the cellular membranes of the compromised cells facilitate the adherence and subsequent retention of crystals, which is instrumental in the pathogenesis of kidney stones. The pathways of ROS production are diverse, involving numerous signaling cascades. Recent researchers’ endeavors have elucidated that selective antioxidants can attenuate intracellular ROS concentrations by modulating these intricate signaling cascades. This reduction in ROS levels has been empirically demonstrated to significantly curtail the accumulation of calcium oxalate crystals within renal tissues in animal models, heralding a novel therapeutic paradigm for the amelioration of nephrolithiasis. In this review, we endeavor to elucidate the contributory role of ROS in kidney stone and explore the protective mechanisms by which certain antioxidants safeguard renal function.